The Effect of Work Motivation, Job Satisfaction With Discipline as an Intervening Variable on the Performance of Government Employees - Hastuti, Sri (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study aims to examine the effect of work motivation and job satisfaction on employee performance with work discipline as mediation. The sample used was employees of the Natuna Regency Public Works and Spatial Planning Office, totaling 60 people. The analysis method used is Partial Least Square (PLS) which shows work motivation has a positive and significant effect on work discipline, job satisfaction has a positive and significant effect on employee work discipline, job satisfaction has a positive and significant effect on employee work discipline, work motivation has a positive and insignificant effect on employee performance, job satisfaction has a positive and insignificant effect on employee performance, and work discipline has a positive and significant effect on employee performance,meanwhile, the indirect influence of work discipline is able to mediate the influence of work motivation on employee performance, and work discipline is able to mediate job satisfaction on employee performance